2011
DOI: 10.1089/thy.2010.0307
|View full text |Cite
|
Sign up to set email alerts
|

Parvovirus B19 Infection in Hashimoto's Thyroiditis, Papillary Thyroid Carcinoma, and Anaplastic Thyroid Carcinoma

Abstract: We extend the data available on B19 detection in the thyroid to show a high correlation of virus in another cohort of PTC and HT at the protein level. We also show, for the first time, B19 infection of much more highly aggressive ATC/undifferentiated tumors. Nuclear to cytoplasmic shift in B19 protein in cancer tissue suggests a possible link between B19 and thyroid cancer pathogenesis/progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
2
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 35 publications
2
30
2
1
Order By: Relevance
“…1 In children, B19 infection is generally associated with erythema infectiosum ("slapped cheek" or fifth disease). 1,2 In immunocompromised or hemolytic subjects, clinical manifestations following B19 infection include polyarthropathy, 3 hematological disorders, such as red cell aplasia and chronic anemia, 4 thrombocytopenia 5 and neutropenia, 6 myocarditis, 7 hepatitis, 8 neurologic diseases, [9][10][11] hyperthyroidism and thyroid cancer pathogenesis/progression, 12,13 glomerulonephritis, 14,15 and systemic lupus erythematosus. 16 On the whole, B19 infection may lead to disorders exhibiting striking similarities with systemic autoimmune diseases, and can be associated with elevated serum autoantibody titers.…”
Section: Introductionmentioning
confidence: 99%
“…1 In children, B19 infection is generally associated with erythema infectiosum ("slapped cheek" or fifth disease). 1,2 In immunocompromised or hemolytic subjects, clinical manifestations following B19 infection include polyarthropathy, 3 hematological disorders, such as red cell aplasia and chronic anemia, 4 thrombocytopenia 5 and neutropenia, 6 myocarditis, 7 hepatitis, 8 neurologic diseases, [9][10][11] hyperthyroidism and thyroid cancer pathogenesis/progression, 12,13 glomerulonephritis, 14,15 and systemic lupus erythematosus. 16 On the whole, B19 infection may lead to disorders exhibiting striking similarities with systemic autoimmune diseases, and can be associated with elevated serum autoantibody titers.…”
Section: Introductionmentioning
confidence: 99%
“…There have been 3 case studies and a fourth group study linking thyroid diseases with B19 [33][34][35][36]. Our laboratory and others have shown that B19 infects the thyroid [37][38][39]. The thyroid's critical role in early neurological development may be altered by B19 infections [40].…”
Section: Infection Of Other Organs and Its Resulting Effect On Brainmentioning
confidence: 99%
“…Herpes simplex virus type 2 was found to be significantly associated with papillary thyroid cancer and the presence of lymph node metastases [22]. Furthermore, human parvovirus B19 has been frequently present in thyroid tissues of Hashimoto’s thyroiditis and papillary thyroid cancer [23]. Although the thyroid gland is one of the CMV reservoirs [12,13], no previous study has examined the presence of CMV in thyroid cancer.…”
Section: Discussionmentioning
confidence: 99%